Moderated-mediation analysis of multimorbidity and health-related quality of life among the Chinese elderly: The role of functional status and cognitive function - Li, Tongxing; Hu, Wei; Zhou, Liang; Peng, Liuming; Cao, Lei; Feng, Zhaolong; He, Qida; Chu, Jiadong; Chen, Xuanli; Liu, Siyuan; Han, Qiang; Sun, Na; et al. (Frontiers in Psychology, 2022)
Objectives: To investigate the relationship between multimorbidity and health-related quality of life (HRQoL), and explore the effects of functional status and cognitive function on Chinses elderly behind this relationship. Methods: The Multivariate logistic regression and Tobit regression models were used to determine the influence of multimorbidity on HRQoL. Bootstrap analysis was used to probe the mediating effects of functional status and the moderating role of cognition on multimorbidity and HRQoL. Results: of the 2887 participants age ≥ 60 years included in the analysis, 51.69% had chronic diseases. Stroke (β= -0.190; 95% confidence interval [CI] = -0.232, -0.149; P < 0.001) and the combination of hypertension and stroke (β = -0.210; 95% CI, -0.259, -0.160; P < 0.001) had the greatest influence on HRQoL. Functional status partially mediated the relationship between the number of non-communicable diseases (No. of NCDs) and HRQoL, while cognitive function had a moderating effect not only in the A-path (No. of NCDs to functional status, β = 0.143; t = 7.18; P < 0.001) and but also in the C-path (No. of NCDs to HRQoL, β = 0.007; t = 6.08; P < 0.001). Conclusions: Functional status partially mediated the relationship between multimorbidity and HRQoL in older adults. And cognitive function, if declined, may strengthen this relationship. These findings suggested that improving cognitive function and functional status in those who developed multimorbidity could be a viable prevention or treatment strategy to improve HRQoL in elderly patients.